Ginger (Zingiber officinale) Root Extract During Pregnancy: A Clinical Feasibility Study - Laekeman, Gert Maria; Van Calsteren, Kristel; Devlieger, Roland; Sarafanova, Ekaterina; Van Limbeek, Jonice; Dierckxsens, Yvan (Planta Medica, 2021)
There is almost no experience with concentrated ginger extracts during pregnancy. The purpose of this trial was to include 50 pregnant women in a clinical feasibility study with EXT.GR10, a 10 × concentrated ethanolic extract of ginger root. The primary objective was to detect complications in the mother during pregnancy and malformations or complications in the newborn at delivery. The secondary purpose was to evaluate the satisfaction of the patients. In total, 51 pregnant women were included in this observational study. They could freely use ginger tablets with a maximum of 2 tablets of 50 mg EXT.GR10 a day in case of gastrointestinal discomfort. Tablets were taken by 44 patients. Stillbirth, prematurity, hypertension, and gestational diabetes occurred. There were no serious complications at birth. In the newborn, 4 cases of dysplasia of the hip were seen and 2 minor malformations. There was no relation between events affecting mother and child and the number of EXT.GR10 tablets taken. About ⅔ of patients appreciated the effects of ginger. This is the first clinical study with the EXT.GR10 extract. Based on this feasibility study, a follow-up clinical trial is planned with a fixed minimum of exposure to EXT.GR10 during the first trimester of pregnancy.
Keywords: ginger; Zingiber officinale; Zingiberaceae; pregnancy; extract; safety